The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.annemergmed.2014.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Intercepting Wrong-Patient Orders in a Computerized Provider Order Entry System

Abstract: Study Objective We evaluated the short- and long-term impact of a computerized provider entry (CPOE)-based patient verification intervention to reduce wrong-patient orders in five emergency departments. Methods A patient verification dialog appeared at the beginning of each ordering session, requiring providers to confirm the patient's identity after a mandatory 2.5–second delay. Using the retract-and-reorder technique, we estimated the rate of wrong-patient orders before and after the implementation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 22 publications
1
45
0
Order By: Relevance
“…Additional strategies aimed at preventing wrong-patient orders include using electronic decision support to verify patient identification before placing orders or alerting providers when orders are not consistent with the diseases listed in the problem list. 6,21,22 However, these interventions can be costly, dependent on the type of CPOE system, and their effectiveness may diminish over time due to alert fatigue. 23 Replacing a nondistinct naming convention with one that uses distinct names is a simple and effective intervention that is not costly, labor intensive, or dependent on new technology and may be easily implemented in most NICUs.…”
Section: Discussionmentioning
confidence: 99%
“…Additional strategies aimed at preventing wrong-patient orders include using electronic decision support to verify patient identification before placing orders or alerting providers when orders are not consistent with the diseases listed in the problem list. 6,21,22 However, these interventions can be costly, dependent on the type of CPOE system, and their effectiveness may diminish over time due to alert fatigue. 23 Replacing a nondistinct naming convention with one that uses distinct names is a simple and effective intervention that is not costly, labor intensive, or dependent on new technology and may be easily implemented in most NICUs.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 For a variety of reasons, the health information technology industry and its ostensible regulators have failed to address safety issues such as this in substantive ways, despite multiple calls to do so. 2,[20][21][22][23] Given that failure, it is unfair and misguided to heap criticism on kludges as solutions to safety problems because the real problem-poor designs based on idealized models of work 24 uninformed by careful ecological analyses of work as actually performed 25 -is beyond the remit of teams such as Green et al 5 The authors here have done the best they could to address a serious problem with the means at their disposal. They took pains to make their intervention more effective, and to minimize the burden it placed on clinicians.…”
mentioning
confidence: 99%
“…But the same interventions can also potentially harm patients, whether by misdiagnosis (1), medication errors (2), medication overdoses (3), or charting/ordering on the wrong patient (4). A study of factors contributing to errors in Swedish Emergency Departments (ED) found that human error and the ED environment, driven by lack of standard procedures, lack of resources and high workload, were major factors (5).…”
Section: Introductionmentioning
confidence: 98%